2016
DOI: 10.1016/j.socscimed.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality and the ‘East-West’ divide in contraception: An analysis at the individual, the couple, and the country level

Abstract: Despite generally low fertility rates in Europe, contraceptive behavior varies to a substantial extent. The dichotomy between Western, and Central and Eastern European countries is particularly relevant.Whereas the former are characterized by the widespread use of modern contraception, the latter show a high prevalence of traditional methods to control fertility. The current study aims to examine whether these differences can be attributed to differences in women's individual status, and in gender inequality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…Gender equality—here defined as the extent to which women and men have an equal share of paid work, money and decision‐making power in society—varies considerably across European and North American countries; Scandinavian countries typically have the highest rates of gender equality and eastern European countries the lowest . Among adults, macro‐level gender equality is associated with higher rates of contraceptive use, including condom and pill use . Gender equality may be linked to contraceptive use among adults through its associations with more equal distribution of resources (including power) within heterosexual romantic relationships, better communication between sexual partners and more egalitarian gender norms in society .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender equality—here defined as the extent to which women and men have an equal share of paid work, money and decision‐making power in society—varies considerably across European and North American countries; Scandinavian countries typically have the highest rates of gender equality and eastern European countries the lowest . Among adults, macro‐level gender equality is associated with higher rates of contraceptive use, including condom and pill use . Gender equality may be linked to contraceptive use among adults through its associations with more equal distribution of resources (including power) within heterosexual romantic relationships, better communication between sexual partners and more egalitarian gender norms in society .…”
Section: Introductionmentioning
confidence: 99%
“…As women's resources rise relative to those of men, their engagement in the contraceptive decision‐making process increases. Given that women are generally more concerned about contraception than men because of their reproductive risk, contraceptive use may be higher in countries in which women have a more equal say in method choice. In addition, more egalitarian gender norms further support women in taking a more active role in contraceptive decision making .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, however, there has been a surge in studies assessing contextual effects on health behaviors. Researchers have found that the characteristics of a community influence the practice of health behaviors including modern contraceptive use (Dereuddre, Van de Velde, & Brackle, 2016;Janevic, Pallas, Ismayilova, & Bradley, 2012;Kaggwa, Diop, & Storey, 2008;Stephenson, Baschieri, Clements, Hennink, & Madise, 2007). For example, Dereuddre et al (2016) found that country-level gender equality was positively associated with modern contraceptive use among European women.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that the characteristics of a community influence the practice of health behaviors including modern contraceptive use (Dereuddre, Van de Velde, & Brackle, 2016;Janevic, Pallas, Ismayilova, & Bradley, 2012;Kaggwa, Diop, & Storey, 2008;Stephenson, Baschieri, Clements, Hennink, & Madise, 2007). For example, Dereuddre et al (2016) found that country-level gender equality was positively associated with modern contraceptive use among European women. Also, Janevic et al (2012) found that among women living in 10 European and Asian countries, women who live in poor communities were less likely to report modern contraceptive use compared to those who live in wealthier communities.…”
Section: Introductionmentioning
confidence: 99%